2016
DOI: 10.1164/rccm.201505-0998oc
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Response to Losartan and Continuous Positive Airway Pressure in Hypertension and Obstructive Sleep Apnea

Abstract: Losartan reduced BP in OSA, but the reductions were less than in no-OSA. Add-on CPAP therapy resulted in no significant changes in 24-hour BP measures except in patients using CPAP efficiently. Clinical trial registered with www.clinicaltrials.gov (NCT00701428).​

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 43 publications
5
52
0
5
Order By: Relevance
“…Even with this modest effect, epidemiological studies have shown that a similar (4 mm Hg) reduction in night-time BP is associated with a 10% reduction in stroke and 22% reduction in coronary heart disease among subjects aged <60 years 33. This additive effect of CPAP in improving BP has been demonstrated in other studies,10 12 34 35 although they have not all shown improvements in sleep SBP—the most important prognostic marker of cardiovascular disease 17…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Even with this modest effect, epidemiological studies have shown that a similar (4 mm Hg) reduction in night-time BP is associated with a 10% reduction in stroke and 22% reduction in coronary heart disease among subjects aged <60 years 33. This additive effect of CPAP in improving BP has been demonstrated in other studies,10 12 34 35 although they have not all shown improvements in sleep SBP—the most important prognostic marker of cardiovascular disease 17…”
Section: Discussionmentioning
confidence: 53%
“…Meta-analyses indicate that CPAP, the gold standard treatment for OSA, results in only a modest 1–2 mm Hg reduction in blood pressure (BP),7 8 in part due to poor long-term adherence with this therapy 9. On the other hand, pharmacotherapy with antihypertensive medication results in much larger BP reductions in patients with sleep apnoea,10 11 but not as pronounced as in hypertensive patients without OSA 12. Despite this, in patients with treatment-resistant hypertension, where the use of multiple antihypertensives has failed, the prevalence of unrecognised sleep apnoea is very high, with reports of up to 83% 13.…”
Section: Introductionmentioning
confidence: 99%
“…The 24 h BP measurements are more sensitive to therapeutic interventions and provide specific prognostic information. This is particularly true in sleep apnoea-related hypertension 18 43 44. While negative in terms of the primary outcome, our study provides interesting insights regarding 24 h ABPM that might be of clinical relevance and a strong rationale for further studies.…”
Section: Discussionmentioning
confidence: 78%
“…Such studies are contributing to our understanding of the pathways by which OSA leads to hypertension and help in choosing the most appropriate antihypertensive agents for patients with OSA. 114 The consequences of not identifying OSA in resistant hypertensive patients are significant. In a retrospective cohort study of over 450 000 hypertensive patients, Bhandari et al 115 reported an increased risk of adverse cardiovascular events in those subjects with sleep apnoea and resistant hypertension compared with those with sleep apnoea and non-resistant hypertension, specifically ischaemic cardiac events and congestive heart failure.…”
Section: Osa Co-morbidities and The Impact Of Cpapmentioning
confidence: 99%